Dried Leaves, Endless Possibilities: A Modern Craft Workshop at SMP Muhammadiyah Ahmad Dahlan Metro - purnawah, heppi; Suci Riya Safitri; Rully Paradise; Fitri Setya Ningsih; Djihad Mujiono (Jurnal Abdimas Nusantara, 2024)
ABSTRACT   The "Dry Leaves, Endless Possibilities" A Modern Craft workshop, program demonstrates how organic waste, such dry leaves, can be turned into artistic craft items with practical, aesthetic, and business potential. This program is intended to foster students' creativity, environmental consciousness, and entrepreneurial spirit through cooperation between Muhammadiyah Ahmad Dahlan Metro Middle School's fine arts teachers and teaching assistance students University Muhammadiyah Kotabumi. Students are guided through the phases of material collection, creative processes, and finishing using a qualitative descriptive method. Technical abilities like soaking, boiling, drying, and dying dried leaves were successfully improved by this program. Additionally, economically significant objects like wall hangings, tissue boxes, and flower vases were made by drilling students. The findings indicate a rise in pupils'.